Keterbatasan Lingkungan dan Keberingasan Sosial - S. Boedhisantoso (Antropologi Indonesia, 1999)
The author looks into the problem of violent conflict and shows it links to a number of factors which include industrialization; crime; social, economic and political pressure; police violence and social entropy. Population pressures have led to environmental scarcity, leaving some groups with no ability to compete for resources. The larger part of the population lacks capital, as well as strategies for acquiring needed resources. These conditions invite violent conflict, as the less fortunate turn to violent action to survive. The problem is made worse by an industrialization without ethics, whereby the absence of guidelines for healthy competition increases the gap between capital holders and the larger population. At present, many of the conflicts that arise are attributed to social disequilibrium, and not to the rise in demand for basic needs. The author argues that a totally equilibrium state does not and cannot exist, even in hunter and gatherer societies that are purported to be egalitarian. Therefore, he suggests that what is needed are social institution that can guaranteed social justice, political democracy and cultural freedom instead.